„Wie ich in meinem Lande bin, so ist mein Land in mir“. Constantin Brunner im holländischen Exil 1933–1937 - Baltschev, Bettina (Aschkenas, 2019)
Abstract: „Even before, in May 1933, the new Nazi regime in Germany began to ostracize, and burn the books of, so-called »un-German« authors, Constantin Brunner went into exile in The Hague. That he decided to go to the Netherlands is not surprising. The Netherlands were the homeland of Baruch de Spinoza, whose thinking is the most important influence on Brunner’s philosophical work. In The Hague he continued his philosophical studies and exchanged opinions and countless letters with friends, companions and followers in all corners of the world. But although Constantin Brunner was out of harm’s way and was, even in exile and far from home, able to dedicate himself wholly to his work, his health declined rapidly. He died on August 27, 1937. But his work has survived in The Hague where, in 1947, Magdalena Kasch founded the »Internationaal Brunner Instituut«.“
Keywords: Den Haag; Deutscher Flüchtling; Exil; Juden; Judenverfolgung; Philosophie

Plessner – Wanderer in Holland - Glastra van Loon, Jan (Plessner in Wiesbaden, 2014)
Keywords: Groningen; Hochschule; Judenverfolgung; Plessner; Helmuth (1892–1985); Universität Groningen; Versteck